Programs as Polypeptides - Williams, Lance R (Artificial life, 2016)
Object-oriented combinator chemistry (OOCC) is an artificial chemistry with composition devices borrowed from object-oriented and functional programming languages. Actors in OOCC are embedded in space and subject to diffusion; since they are neither created nor destroyed, their mass is conserved. Actors use programs constructed from combinators to asynchronously update their own states and the states of other actors in their neighborhoods. The fact that programs and combinators are themselves reified as actors makes it possible to build programs that build programs from combinators of a few primitive types using asynchronous spatial processes that resemble chemistry as much as computation. To demonstrate this, OOCC is used to define a parallel, asynchronous, spatially distributed self-replicating system modeled in part on the living cell. Since interactions among its parts result in the construction of more of these same parts, the system is strongly constructive. The system's high normalized complexity is contrasted with that of a simple composome.